Characteristic crystal orientation of folia in oyster shell, Crassostrea gigas - Lee, Seung Woo; Kim, Gyeung Ho; Choi, Cheong Song (ELSEVIER SCIENCE BV, 2008)
The thin sheets of calcite, termed folia, that make up much of the shell of an oyster are composed of foliated lath. Folia of the giant Pacific oyster (Crassostrea gigas) were examined using TEM (transmission electron microscopy) and tested using microindentation and nanoindentation techniques. Analysis of the Kikuchi patterns obtained from the folia showed that there are two types (type I and type II) of preferred orientation, with an angle of around 70 degrees between them. Nanoindentation tests showed that the folia exhibit a hardness of about 3 GPa and elastic modulus of about 73 GPa. Microcracks were generated using a microindenter in order to study the fracture mechanisms of the folia. Following on from these investigations, fracture mechanisms are discussed in conjunction with the correlation between preferred orientation and structural characteristics during cracking of the folia. Comparing the morphology and the polymorphism with nacre (also known as mother of pearl), the advantages of the relatively fast crystal growth and less amount of organic matrix in folia may have interesting implications for the development of sophisticated synthetic materials. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: CALCITIC SPONGE SPICULES; DESIGN STRATEGIES; MOLLUSK SHELL; NACRE; GROWTH